2022
DOI: 10.1007/s10639-022-11122-4
|View full text |Cite
|
Sign up to set email alerts
|

Tailored gamification in education: A literature review and future agenda

Abstract: Gamification has been widely used to design better educational systems aiming to increase students’ concentration, motivation, engagement, flow experience, and others positive experiences. With advances in research on gamification in education, over the past few years, many studies have highlighted the need to tailor the gamification design properties to match individual students’ needs, characteristics and preferences. Thus, different studies have been conducted to personalize the gamification in education. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
5

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 81 publications
0
37
0
5
Order By: Relevance
“…Artificial Intelligence approaches are grouped into two categories: AI algorithm and AI model/framework [47], as shown in Figure 7. Algorithms including supervised, unsupervised, reinforcement, personalized, and built‐in algorithms are categorized under AI algorithm and the frameworks including adaptive, proposed, and reinforcement frameworks and models including existing and proposed model are categorized under AI framework/model.…”
Section: Literature Review Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial Intelligence approaches are grouped into two categories: AI algorithm and AI model/framework [47], as shown in Figure 7. Algorithms including supervised, unsupervised, reinforcement, personalized, and built‐in algorithms are categorized under AI algorithm and the frameworks including adaptive, proposed, and reinforcement frameworks and models including existing and proposed model are categorized under AI framework/model.…”
Section: Literature Review Methodologymentioning
confidence: 99%
“…However, the success of e‐learning is negatively correlated with learning motivation, training material, in‐person interactions, and ease of use. To increase concentration, motivation, engagement, flow, and other positive experiences, gamification has been widely used in the educational system [47]. Gamification is adding game‐like activities in nongame settings [56] with various gamification elements such as points, badges, leaderboards, avatars, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Research on gamification wasn't directly affected by the global pandemic but left a profound impact on the education world: classrooms were forcibly held online, and teachers and professors had to step up to the challenge with new ways to conduct a classroom. For this reason, gamification tools have been tried along with different strategies, such as microlearning and flipped classrooms (Ekici, 2021; Oliveira et al., 2023). In contrast, companies couldn't introduce game elements in the workplace for learning, as the main application until 2020 was mostly on training sessions or brief events (Hamari et al., 2014; Koivisto and Hamari, 2019; Bakhanova et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, various studies that applied gamification technique in the education area had been conducted. Previous study was also carried out on the transformation of education system to achieve motivational benefits the way games function to human being as well as relating it to investigating the gamification effect on students' learning experience (Seixas et al, 2016;Oliveira et al, 2022). Nonetheless, despite the results of previous studies showing increase in student engagement and motivation after using gamification technique in education (Koivisto and Hamari, 2019;Bai et al, 2020;Sailer and Homner, 2020), there are also studies that revealed the opposite effect of gamification such as discouragement and learning outcome impairment in certain set of students as found in the study of (Hanus and Fox, 2015;Toda et al, 2017;Kwon and Özpolat, 2021).…”
Section: Gamification In Educationmentioning
confidence: 99%